Functional traits and growth rate response to stand variables: differences between saplings and seedlings of native trees established in loblolly pine plantations in the Atlantic Forest - Ritter, Luis Javier; Medina, Micaela; Goya, Juan; Campanello, Paula Inés; Pinazo, Martin Alcides; Arturi, Marcelo Fabián (Springer, 2022)
The establishment of native trees in exotic forest plantations can improve economic and ecological outcomes, and functional traits can help understanding differential responses of growth rates to stand variables. It is well known that growth rates can depend on functional traits and that the associations between functional traits and plant growth vary across ontogenetic stages. Here we studied if the response of growth rate to stand variables, that reflect ecological conditions, is associated with wood density, seed mass and height at maturity and if such relationships differ between saplings and seedlings. We measred the stem diameter increment over two years in 164 seedlings and 290 saplings of 30 tree species in 9 lobolly pine plantations in the Atlantic Forest, Argentina. The relationship between stem diameter increment and stand basal area, mean canopy openness and stand age was evaluated. The growth rate of saplings decreases with basal area and increased with canopy openness in species with wood density < 0.56 g.cm-3 or height at maturity > 23 m. No differences in growth rate response were found along seed mass. No consistent relationships between growth rate and stand variables were found in seedlings. We concluded that seedling growth rate is unrelated to stand variables while responsive species at sapling stage are those with low wood density or medium-high height at maturity. Silvicultural treatments reducing basal area can benefit the planted trees as well as unplanted saplings of medium-heigh valued native trees.